Symmetry breaking of a matter-wave soliton in a double-well potential formed by spatially confined spin-orbit coupling. (January 2020) - Ye, Zhi-Jiang; Chen, Yi-Xi; Zheng, Yi-Yin; Chen, Xiong-Wei; Liu, Bin
Highlights: Verify the SBB in DWP which constructed by spatially confined spin-orbit coupling. Displacement and bimodal symmetry breaking are found in this system. The influence on the SBB induced by the Galilean transformation are studied. Abstract: We consider the symmetry breaking of a matter-wave soliton formed by spinor Bose-Einstein condensates (BECs) illuminated by a two-spot laser beam. This laser beam introduces spin-orbit (SO) coupling in the BECs such that the SO coupling produces an effect similar to a linear double-well potential (DWP). It is well known that symmetry breaking in a DWP is an important effect and has been discussed in many kinds of systems. However, it has not yet been discussed in a DWP formed by SO coupling. The objective of this work is to study the symmetry breaking of spinor BECs trapped by a DWP formed by SO coupling. We find that two kinds of symmetry breaking, displacement symmetry breaking and bimodal symmetry breaking, can be obtained in this model. The influence of the symmetry transition is systematically discussed by controlling the interaction strength of the BECs and the distance between the center of the two spots. Moreover, because SO coupling violates Galilean invariance, the influence of symmetry breaking in the moving system is also addressed in this paper.